SPATIAL AND TEMPORAL VARIABILITIES OF SURFACE WATER QUALITY IN URBAN AND RESIDENTIAL AREAS IN AN GIANG, VIETNAM (TẠP CHÍ KHOA HỌC TRƯỜNG ĐẠI HỌC TRÀ VINH, 2022)
This study aims to assess the surface water quality in both residential areas and urban areas in An Giang Province from 2011to 2019. Thirteen locations were selected with eight water quality variables at each location; which were temperature, pH, nitrate (NO3--N), total suspended solids (TSS), biochemical oxygen demand (BOD) and chemical oxygen demand (COD), coliforms, and total oil and grease were collected. Surface water quality data were compared with the Vietnamese standards. Cluster analysis (CA) and principal component analysis (PCA) were applied to determine the sampling locations and water variables affecting waterquality in the residential and urban areas. The results showed that the parameters of temperature, pH, and NO3- - N were within the allowable limits - while TSS, BOD, COD, coliforms, and total oil and grease exceeded the permitted limit. The results of CA indicated that 13 sampling points could be reduced to 8, saving nearly 40% of the water quality monitoring costs which could be provided the cost for water treatment of water bodies. PCA revealed that at least three sources of pollution could explain 83.7% of the water quality fluctuations. The main sources that affected surface water quality in residential and urban areas could be wastewater, solid wastes, stormwater runoff, and other hydrological factors. Further studies need to investigate and curb the sources of water pollution. It is urgently required to build a system of waste collection and treatment in this study area and at the same time raise public awareness about environmental protection.